Santri and Jihad Algorithm: The Production of Da’wah Content on Instagram Stories - Nurwahid, Aditya Fahmi; Setiawan, Veri (LPPM IAIN Parepare, 2022)
Jihad Algoritma defined as a movement that push the academician, moslem micro-influencer, local Da’I, Santri, and moslem community in common to create more da’wah content in social. This movement aimed to compete the algorithm of social media that also promote ‘negative content’ based on Islamic value standart, to create creative, viral, and engaged content. This research aimed to explore the production of dakwah content on Santri’s Instagram Story. Using the perspective of phenomenological research, it portrays santri experience on using Instagram Story as a medium of communication and da’wah in conveying information and religious messages to the public. Results showed three indicators on Da’wah Content production in Instagram Story. The concern of the creators are: 1) the content development, 2) the form of remediation, and also 3) to adjusted the content algorithm and jihad spirit on the da’wah activity. Santri planned the development of content on every account. The plan are organized based on the characteristic of Instagram Story as the main media. The da’wah message adjusted on Instagram Story characteristics. Then, algorithm consideration and jihad spirits on every santri’s community evaluates how the content production and content development, based on the development of account and the content plan implementation.